The study of psychometric properties of the DASI in patients with heart failure - Fatemeh Omrani; Naiire Salmani; Somayeh Kahdouei (Tehran University of Medical Sciences, 2022)
Background & Aim: Performing daily activities is a major element of quality of life in heart failure patients. The Duke Activity Status Index (DASI) is a tool to measure factional capacity. We aimed to examine the psychometric properties of the DASI in patients with heart failure. Methods & Materials: In this methodological study using convenience sampling, we included 120 patients with heart failure referred to the heart clinic of Afshar hospital, Yazd in 2018.  We first translated the original DASI to Farsi using forward and backward translation method. Then, we evaluated its face validity, content validity, criterion-related validity, construct validity (Exploratory Factor Analysis), and reliability (internal consistency). Results: In quantitative content validity, the content validity index and content validity ratio were confirmed. The criterion-related validity was confirmed using the Spearman correlation coefficient between the New York Heart Association functional classification scores and the DASI score (r=-0.77, P<0.001) with a significant correlation. To assess construct validity, exploratory factor analysis revealed two factors, explaining 52.61% of the total variance. Factor 1 included items with high MET values and factor 2 included those with low MET values. The reliability of the DASI was determined using the Cronbach's alpha coefficient that was 0.81. Conclusion: The DASI is of good validity and reliability and due to its appropriate psychometric properties, this tool can be used to evaluate the functional status of patients with heart failure.